Persepsi Guru Terhadap Peran Sekolah Sebagai Komunitas Belajar Profesional Dalam Perspektif Guru Sekolah Menengah Negeri Di Wilayah Jakarta Pusat - Heldy Ramadhan Putra Pembangunan; Winda Dewi Listyasari; Evitha Soraya (Program Studi Manajemen Pendidikan, 2018)
This study aims to examine teachers’ perceptions of professional learning community. The study was conducted from July 2017 – October 2017 in six state senior high schools in Central Jakarta. The method employed in this study was descriptive quantitative. The samples of this research were 108 teachers in Central Jakarta was determined by purposive sampling technique. Data were collected by using Professional Learning Communities Assessment – Revised developed by Olivier, D.F., & Hipp, K.K. (2010) that has been translated into Bahasa Indonesia. The research found that there were 60 teachers (54%) have high perceptions on school as professional learning community, while 48 teachers (44%) have low perceptions. Subsequently, based on the analysis of each dimension, all the dimensions of the professional learning community variables were perceived low by the teacher. The lowest dimension is shared personal practice